Human prion strain selection in transgenic mice - Giles, Kurt (2010)
Transgenic (Tg) mice expressing chimeras of mouse and human prion proteins (PrP) have shorter incubation periods for Creutzfeldt-Jakob disease (CJD) prions than mice expressing full-length human PrP. Increasing the sequence similarity of the chimeric PrP to mouse PrP, by reverting human residues to mouse, resulted in a Tg line, denoted Tg22372, which was susceptible to sporadic (s) CJD prions in ~110 days 1. Reversion of one additional residue (M111V) resulted in a new Tg line, termed Tg1014, susceptible to sCJD prions in ~75 days. Tg1014 mice also has shorter incubation periods for variant (v) CJD prions, providing a more tractable model for studying this prion strain. Transmission of vCJD prions to Tg1014 mice resulted in two different strains, determined by neuropathology and biochemical analysis, which correlated with the length of the incubation time. One strain had the biochemical, neuropathological, and transmission characteristics including longer incubation times of the inoculated vCJD strain; the second strain produced a phenotype resembling that of sCJD prions including relatively shorter incubation periods. Mice with intermediate incubation periods for vCJD prions had a mixture of the two strains. Both strains were serially transmitted in Tg1014 mice, which led to further reduction in incubation periods. Conversion of vCJD-like to sCJD-like strains was favored in Tg1014 mice more than in the Tg22372 line. The single amino acid difference therefore appears to offer selective pressure for propagation of the sCJD-like strain. These two Tg mouse lines provide relatively rapid models to study human prion diseases as well as the evolution of human prion strains.